2015
DOI: 10.1186/s12891-015-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in rabbit meniscus and bone marrow exhibit a similar feature but a heterogeneous multi-differentiation potential: superiority of meniscus as a cell source for meniscus repair

Abstract: BackgroundThe restoration of damaged meniscus has always been a challenge due to its limited healing capacity. Recently, bone marrow-derived mesenchymal stem cells (BMSCs) provide a promising alternative to repair meniscal defects. However, BMSCs are not ideal chondroprogenitor cells for meniscus repair because they have a high propensity for cartilage hypertrophy and bone formation. Our hypothesis is that mesenchymal stem cells (MSCs) reside in meniscus maintain specific traits distinct from others which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 47 publications
1
43
0
1
Order By: Relevance
“…The histological outcomes confirmed formation of the hyaline cartilage-like tissue expressing collagen type II [55,56,58,59] as well as collagen type I [55,56,58]. Note that, the latter is a marker of fibrocartilaginous tissue.…”
Section: Pre-clinical Studies In Animal Modelmentioning
confidence: 62%
“…The histological outcomes confirmed formation of the hyaline cartilage-like tissue expressing collagen type II [55,56,58,59] as well as collagen type I [55,56,58]. Note that, the latter is a marker of fibrocartilaginous tissue.…”
Section: Pre-clinical Studies In Animal Modelmentioning
confidence: 62%
“…Exogenous stem cells can in turn stimulate endogenous repair cells to produce new tissue. Previous studies have found that the meniscus itself contains a subpopulation of multipotential cells [23,30,36,64], which can be utilized to regenerate tissue. Moreover, the combination of MSCs with native meniscal cells is known to prevent MSC hypertrophy [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported promising results in meniscal regeneration utilizing meniscus ECM preparations in allograft [16,20,70], hydrogel [43,44], and soluble [46] forms; MSCs derived from the bone marrow [7173], synovium [29], and meniscus [23,31]; and evaluation in animal models ranging from subcutaneous implantation [43,45] to intra-articular injections in rats [29,31,72] up to primates [74]; but none have studied the combination of MSCs and meniscus ECM hydrogel at their relevant site of action. We demonstrate the use of decellularized bovine meniscus hydrogel for intra-articular delivery of human mesenchymal stem cells in an orthotopic nude rat model of meniscal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells possess self‐renewal capacity and multi‐differentiation potential and have immunosuppressive properties . The inherent capacity for expression of type II collagen by MeSCs is greater than that of BMSCs and SMSCs . Several studies have used MeSCs for meniscus tissue engineering, which has shown much potential for meniscus regeneration, thereby delaying or reducing the progression of OA induced by meniscectomy .…”
Section: Introductionmentioning
confidence: 99%